Malignant perivascular epithelioid cell tumor of the ileum on 18F-fluorodeoxyglucose positron emission tomography/computed tomography with pathological correlation - Das, Jeeban; Bou-Ayache, Jad; Gollub, Marc; Riedl, Christopher; Ulaner, Gary (World Journal of Nuclear Medicine, 2021)
A 75-year-old woman presented with a 1-month history of abdominal pain. Contrast-enhanced computed tomography (CT) demonstrated a large solid mass in the left lower abdominal quadrant, suspicious for malignancy. Staging with 18F-fluorodeoxyglucose (FDG) positron emission tomography/CT imaging demonstrated intense FDG uptake in the mass with no evidence of metastatic disease. Complete surgical resection was performed, and histopathological analysis confirmed a malignant perivascular epithelioid cell tumor of the ileum.
Keywords: 18F-fluorodeoxyglucose; perivascular epithelioid cell tumor; positron emission tomography/computed tomography